Who Collects Art? An International Empirical Assessment - Lasse Steiner; Bruno S. Frey; Magnus Resch (Center for Research in Economics, Management and the Arts (CREMA), 2014)
A unique recent data set covering around 3,000 private art collections and collectors is used to identify their location and composition. The largest number of private collections is located in Europe, followed by North America and Asia. The largest number of private art collections is located in the United States. The United Kingdom, Germany and Spain have more collections per capita of population. Private collectors above all assemble works by artists from North America, followed by Asian, and only then European artists. The three artists most assembled by private collectors are Warhol, Picasso and Hirst. A considerable part of the differences in the number of private collections per head between countries can be attributed to per capita income. The collection of art is mainly undertaken by persons who can afford to build up wealth also in the form of collections of art.
Keywords: Z11; F14; G15; 330; Art; collections; home bias; investment; international finance